2021
DOI: 10.1371/journal.pone.0261230
|View full text |Cite
|
Sign up to set email alerts
|

A method for campus-wide SARS-CoV-2 surveillance at a large public university

Abstract: The systematic screening of asymptomatic and pre-symptomatic individuals is a powerful tool for controlling community transmission of infectious disease on college campuses. Faced with a paucity of testing in the beginning of the COVID-19 pandemic, many universities developed molecular diagnostic laboratories focused on SARS-CoV-2 diagnostic testing on campus and in their broader communities. We established the UC Santa Cruz Molecular Diagnostic Lab in early April 2020 and began testing clinical samples just f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 30 publications
(26 reference statements)
0
14
0
Order By: Relevance
“…Despite initial problems relating to technology, tools and training for both staff and students ( 2 ), progress was made during the digital transition ( 4 ), but how to safely reopen educational institutions quickly became a major concern ( 5 , 6 ). To be able to resume in-person activities, many universities developed a COVID-19 Task Force with an illness response procedure and applied a health protocol that included social distancing and face-mask use; some even offered an optional on-campus testing program to identify and isolate cases promptly ( 7 , 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…Despite initial problems relating to technology, tools and training for both staff and students ( 2 ), progress was made during the digital transition ( 4 ), but how to safely reopen educational institutions quickly became a major concern ( 5 , 6 ). To be able to resume in-person activities, many universities developed a COVID-19 Task Force with an illness response procedure and applied a health protocol that included social distancing and face-mask use; some even offered an optional on-campus testing program to identify and isolate cases promptly ( 7 , 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…Our LOD is lower than that reported for SalivaDirect (6-12 SARS-CoV-2 copies per µL) 24 , which has a similar sample work ow, but relies on the less sensitive RT-qPCR platform 37 . Most other screening assays report LODs within this range as well (0.5-10.6 copies per µl) 12,13,14,15,16,17,18 . For pooled samples our LOD was 12 copies per µl, which is in line with at least one other report 16 and considered an acceptable trade-off for screening assays in which frequency and turnaround time rather than sensitivity are more important for mitigation of viral spread 38 .…”
Section: Discussionmentioning
confidence: 88%
“…To facilitate efforts to return to in-person learning, routine screening was proposed to identify infected, asymptomatic individuals and, in combination with other interventions, mitigate the spread of SARS-CoV-2 2 . Many universities developed or implemented screening assays, using a variety of sample types (saliva vs nasal swabs), sample processing (minimal vs RNA extraction), e ciency strategies (pooled vs unpooled), and platforms (qPCR, RT-LAMP, antigen tests), although the majority relied on qPCR 3,4,5,6,7,8,9,10,11,12,13,14,15,16,17,18 . A recent analysis of 1,400 institutions of higher education (IHE) showed that the success of these screening efforts extended to their housed counties, as those with IHEs that conducted widespread testing had fewer hospitalizations and deaths 19 .…”
Section: Introductionmentioning
confidence: 99%
“…For example, epidemiologic models have concluded that even 20% uptake of facemasks can significantly reduce epidemic size under a full IHE campus re-opening [ 24 ]. Additionally, surveillance testing of campus populations has been associated with lower transmission of SARS-CoV-2 than less frequent or symptomatic-only testing policies [ 26 , 27 ]. While there is evidence that suggests distance-based interventions are not always associated with reduced transmission of SARS-CoV-2 [ 30 ], the literature frequently echoes the finding that physical distancing in combination with other NPIs more effectively prevents COVID-19 than any NPI alone [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%